Analisis Environmental Performance dan Corporate Social Responsibility terhadap Kinerja Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2018-2022 - Anggun Permata Husda; Risca Azmiana; Haposan Banjarnahor (LPPM Universitas Putera Batam, 2023)
The research aims to analyze environmental performance and corporate social responsibility on the Performance of Manufacturing Companies listed on the IDX in 2018-2022. This research uses 34 mining companies listed on the IDX in 2018-2022. The sampling technique used purposive sampling. The sample used was 12 coal mining companies listed on the Indonesia Stock Exchange. The data used is in the form of annual reports and sustainability reports which are reported consistently every year by the company. Process research data using SPSS 29 for partial test (t) and simultaneous test (f). The results of the study show that environmental performance has a significant positive effect on the performance of mining companies listed on the IDX in 2018-2022. Then Corporate Social Responsibility has a significant positive effect on the performance of mining companies listed on the IDX in 2018-2022. Environmental performance and corporate social responsibility simultaneously have a significant positive effect on the performance of mining companies listed on the IDX in 2018-2022.